Explaining Restrictive TANF Policies: Group Threat Hypothesis and State Economy Conditions. Issue 44 (8th August 2018) - Cheng, Tyrone C.; Lo, Celia C.
ABSTRACT: This study examined whether TANF policies' restrictiveness is related to states' racial composition and economic conditions. The data were extracted from various reports dated 2000–2014. Results from generalized least squares random-effects modeling showed the number of restrictive TANF policies to be associated positively with larger populations of Hispanic individuals and associated negatively with larger populations of African American individuals. No association was found between policies' restrictiveness and "other" minority population, nor between restrictiveness and either poverty or unemployment. One conclusion suggested by the analysis is that restrictive TANF policies result from dramatic increases in the Hispanic population that trigger the dominant group's resentment of ethnic minorities. Several policy implications are stated.